Enhanced high temperature wear resistant refractory castable and method of making same

By using a specific combination of raw materials and processes to prepare reinforced high-temperature wear-resistant refractory castables, the problems of strength and high-temperature resistance of existing castables have been solved, achieving high mechanical strength and good heat resistance.

CN120554100BActive Publication Date: 2026-03-17CHANGXING YUNFENG CHARGE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510678757.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2026-03-17
Estimated Expiration
2045-05-26

AI Technical Summary

Technical Problem

Existing refractory castables suffer from low strength and poor high-temperature resistance.

Method used

Reinforced high-temperature wear-resistant refractory castables are prepared by using raw materials such as high-alumina bauxite, andalusite, silica micro powder, silicon nitride micro powder, aluminum tripolyphosphate, alumina micro powder, attapulgite clay, calcium aluminate cement, silica sol, and modified short-cut basalt fiber through specific mixing and sintering processes.

Benefits of technology

It improves the mechanical strength, oxidation resistance, slag resistance and thermal stability of castables, and enhances the density and high temperature resistance of castables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005418579370000031
    Figure BDA0005418579370000031
  • Figure BDA0005418579370000032
    Figure BDA0005418579370000032
  • Figure BDA0005418579370000041
    Figure BDA0005418579370000041
Patent Text Reader

Abstract

The application discloses an enhanced high-temperature wear-resistant and refractory castable, which comprises the following raw materials in parts by weight: high bauxite 84.5-93.6 parts, andalusite 21.4-25.3 parts, silicon oxide micro powder 32.5-37.8 parts, silicon nitride micro powder 23.8-26.2 parts, aluminum tripolyphosphate 6.8-9.2 parts, aluminum oxide micro powder 6.3-10.5 parts, attapulgite clay 1.5-3.2 parts, calcium aluminate cement 11.5-22.4 parts, modified short basalt fiber 15.6-18.4 parts, water reducing agent 5.7-6.5 parts, and silica sol 1.5-3.2 parts; and the application further discloses a preparation method of the enhanced high-temperature wear-resistant and refractory castable; the high bauxite and the andalusite are used as the aggregate, the weight and the thermal conductivity of the castable are reduced, the strength of the castable is improved, the modified short basalt fiber has the advantages of light volume weight, high temperature resistance, good thermal stability, low thermal conductivity, small heat capacity, good mechanical vibration resistance, small thermal expansion, and good heat insulation performance, and the compactness of the castable is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of refractory materials technology, and relates to an enhanced high-temperature wear-resistant refractory castable and its preparation method. Background Technology

[0002] Currently, refractory materials can be divided into shaped refractories and unshaped refractories. Shaped refractories are finished materials that can be directly installed. Unshaped refractories include refractory plastics and refractory castables, which are cast on-site during the construction of refractory structural layers. Among them, refractory castables are convenient to use, easy to construct, and can be prepared on-site or selected from high-performance materials as needed. Therefore, refractory castables are a widely used and widely applicable type of unshaped refractory material in furnace construction engineering.

[0003] Refractory castables are mixtures of refractory aggregates, powders, and binders, which are then poured into the desired form after the addition of water or other liquids. Refractory castables are used in specialized applications such as heating furnaces and soaking furnaces in the steel industry, heat treatment furnaces in the machinery industry, and thermal equipment in the petroleum, chemical, non-ferrous, and building materials industries, as well as for insulation linings and chimney linings. Therefore, these refractory structural layers require good thermal insulation and fire resistance, as well as high mechanical strength. Existing insulating refractory castables suffer from low strength and poor high-temperature resistance due to improper raw material selection and unreasonable particle size distribution. Summary of the Invention

[0004] The purpose of this invention is to provide an enhanced high-temperature wear-resistant refractory castable and its preparation method, thereby solving the problem of poor strength and high-temperature resistance of refractory castables mentioned in the background art.

[0005] The objective of this invention can be achieved through the following technical solutions:

[0006] A reinforced high-temperature wear-resistant refractory castable comprises the following raw materials in parts by weight:

[0007] High-alumina bauxite 84.5-93.6 parts, andalusite 21.4-25.3 parts, silica powder 32.5-37.8 parts, silicon nitride powder 23.8-26.2 parts, aluminum tripolyphosphate 6.8-9.2 parts, alumina powder 6.3-10.5 parts, attapulgite clay 1.5-3.2 parts, calcium aluminate cement 11.5-22.4 parts, modified short-cut basalt fiber 15.6-18.4 parts, water-reducing agent 5.7-6.5 parts, silica sol 1.5-3.2 parts;

[0008] This reinforced high-temperature wear-resistant and refractory castable is made by the following steps:

[0009] Step A1: Add high-alumina bauxite and andalusite into a mixer and mix for 10-15 minutes to obtain mixed aggregate;

[0010] Step A2: The silica micro powder, silicon nitride micro powder, aluminum tripolyphosphate, alumina micro powder, attapulgite clay, calcium aluminate cement, silica sol, water-reducing agent and modified short-cut basalt fiber are ball-milled evenly to obtain a mixed powder.

[0011] Step A3: Add the mixed powder to the mixed aggregate, mix evenly, then add 2-8% of the total weight of the raw materials with water and stir to form a mud. Place the mud into a mold, vibrate and cast it into shape. After hardening at room temperature, demold it and dry it at 120-140℃ for 12-20 hours. Let it cool naturally to room temperature to obtain the green body.

[0012] Step A4: Sinter the green body at 1300-1500℃ for 20-28 hours to obtain reinforced high-temperature wear-resistant refractory castable.

[0013] Furthermore, the high-alumina bauxite has a particle size of 1-2 mm and an alumina content of ≥80% wt.

[0014] Furthermore, the grain size of the andalusite is ≤1mm.

[0015] Furthermore, the particle size of the silica micro powder is ≤0.065mm.

[0016] Furthermore, the particle size of the silicon nitride micro powder is ≤0.06mm.

[0017] Furthermore, the particle size of the alumina micro powder is ≤3μm.

[0018] Furthermore, the water-reducing agent is one of sodium tripolyphosphate, sodium hexametaphosphate, sodium polyacrylate, sodium lignosulfonate, and calcium lignosulfonate.

[0019] The modified short-cut basalt fibers are prepared by the following steps:

[0020] Short-cut basalt fibers are mixed with a high-temperature resistant organic modifier and DMF, and reacted at 60-80℃ for 4-6 hours under N2 protection to obtain modified short-cut basalt fibers.

[0021] Furthermore, the ratio of the chopped basalt fiber, the high-temperature resistant organic modifier, and DMF is 4.5-7.2g: 2.1-2.5g: 80-100mL.

[0022] The high-temperature resistant organic modifier is prepared by the following steps:

[0023] Step S1: Add aminopropyl double-headed compound and tetrahydrofuran to a three-necked flask, purge with nitrogen for protection, add p-hydroxybenzaldehyde and anhydrous sodium sulfate, and heat to 60-65℃ for 8-10 hours to obtain intermediate 1.

[0024] The reaction process is as follows:

[0025]

[0026] Step S2: Add p-aminochlorobenzene and tetrahydrofuran to a three-necked flask, add formaldehyde solution with a mass fraction of 40%-45% under ice-water bath conditions, stir for 0.5-1h, add intermediate 1, heat to 60-65℃, react for 10-12h to obtain intermediate 2.

[0027] The reaction process is as follows:

[0028]

[0029] Step S3: Add 4-nitrobenzaldehyde, nitrobenzane, ammonium acetate, and acetic anhydride to a three-necked flask, heat to 125-130℃ and react for 3-4 hours to obtain intermediate 3;

[0030] The reaction process is as follows:

[0031]

[0032] Step S4: Add intermediate 3,4-nitro-o-phenylenediamine, copper bromide, and n-butanol to a three-necked flask, heat to 110-115℃ and react for 13-14 hours, then reduce with hydrogen to obtain intermediate 4.

[0033] The reaction process is as follows:

[0034]

[0035] The temperature is raised to 60-70℃ and the reaction is carried out for 5-8 hours to obtain a high-temperature resistant organic modifier.

[0036] The reaction process is as follows:

[0037]

[0038] Furthermore, the ratio of aminopropyl double-ended, tetrahydrofuran, p-hydroxybenzaldehyde, and anhydrous sodium sulfate in step S1 is 15.1-16.5g: 100-120mL: 17.1-17.8g: 0.1-0.13g.

[0039] Furthermore, in step S2, the ratio of the amounts of p-aminochlorobenzene, tetrahydrofuran, formaldehyde solution, and intermediate 1 is 4.5-5.2g: 80-100mL: 9.5-10g: 6.3-7.2g.

[0040] Furthermore, in step S3, the ratio of 4-nitrobenzaldehyde, nitrobethanone, ammonium acetate, and acetic anhydride is 20.4-21.3g: 27.8-28.5g: 13.2-13.5g: 70-90mL.

[0041] Furthermore, in step S4, the ratio of intermediate 3,4-nitro-o-phenylenediamine, copper bromide, and n-butanol is 8.7-9.4g: 6.3-6.7g: 0.9-1g: 110-120mL.

[0042] Furthermore, in step S5, the molar ratio of intermediate 4 to intermediate 2 is 1:1, and the amount of potassium carbonate used is 10-15% of the mass of intermediate 4.

[0043] A method for preparing an enhanced high-temperature wear-resistant refractory castable includes the following steps:

[0044] Step A1: Add high-alumina bauxite and andalusite into a mixer and mix for 10-15 minutes to obtain mixed aggregate;

[0045] Step A2: The silica micro powder, silicon nitride micro powder, aluminum tripolyphosphate, alumina micro powder, attapulgite clay, calcium aluminate cement, silica sol, water-reducing agent and modified short-cut basalt fiber are ball-milled evenly to obtain a mixed powder.

[0046] Step A3: Add the mixed powder to the mixed aggregate, mix evenly, then add 2-8% of the total weight of the raw materials with water and stir to form a mud. Place the mud into a mold, vibrate and cast it into shape. After hardening at room temperature, demold it and dry it at 120-140℃ for 12-20 hours. Let it cool naturally to room temperature to obtain the green body.

[0047] Step A4: Sinter the green body at 1300-1500℃ for 20-28 hours to obtain reinforced high-temperature wear-resistant refractory castable.

[0048] The beneficial effects of this invention are as follows: This invention provides an enhanced high-temperature wear-resistant refractory castable and its preparation method. The high-alumina bauxite of this invention has high strength, andalusite is volume stable at high temperatures and does not shrink. Under heating conditions, andalusite can form a good mullite network, exhibiting excellent mechanical strength and slag resistance. The combined use of high-alumina bauxite and andalusite as aggregate reduces the weight and thermal conductivity of the castable, thereby improving its strength. Silica micropowder has a low coefficient of thermal expansion and good wear resistance; silicon nitride micropowder is lubricating, wear-resistant, oxidation-resistant at high temperatures, does not easily conduct heat, and has good resistance to thermal shock. The small particle size of silica micropowder, silicon nitride micropowder, and alumina micropowder allows them to uniformly fill the tiny voids in the castable, improving its oxidation resistance and high-temperature strength. Silica sol is hygroscopic, and attapulgite clay has good leveling properties, strong water absorption, and exhibits stickiness and plasticity when wet. The combined use of silica sol, attapulgite clay, and calcium aluminate cement results in tight adhesion to various materials. Modified chopped basalt fibers possess advantages such as low density, high temperature resistance, good thermal stability, low thermal conductivity, low heat capacity, good resistance to mechanical vibration, low thermal expansion, and good thermal insulation performance, further enhancing the density of castables. The chopped basalt fibers are impregnated and coated with a high-temperature resistant organic modifier, significantly improving the high-temperature resistance of the substrate. This high-temperature resistant organic modifier contains a benzopyrazine heterocyclic structure with high bond energy, large molecular volume, and weak polarity, exhibiting high stability and heat resistance. Furthermore, the high-temperature resistant organic modifier also contains a benzoxazine group organosilicon structure. Through the ring-opening polymerization process of the benzoxazine ring, the intermediate is effectively bonded to the surface of the chopped basalt fibers using a hydrogen bonding strengthening mechanism, improving its wettability and thus enhancing the dispersibility of the chopped basalt fibers in the castable, thereby further improving the strength of the castable. Detailed Implementation

[0049] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0050] Example 1: Modified short-cut basalt fibers were prepared by the following steps:

[0051] 4.5g of chopped basalt fiber was mixed with 2.1g of high-temperature resistant organic modifier and 80mL of DMF, and reacted at 60℃ for 4 hours under N2 protection to obtain modified chopped basalt fiber.

[0052] Example 2: Modified short-cut basalt fibers were prepared by the following steps:

[0053] 6.3g of chopped basalt fiber was mixed with 2.3g of high-temperature resistant organic modifier and 95mL of DMF, and reacted at 70℃ for 6 hours under N2 protection to obtain modified chopped basalt fiber.

[0054] Example 3: Modified short-cut basalt fibers were prepared by the following steps:

[0055] 7.2g of chopped basalt fiber was mixed with 2.5g of high-temperature resistant organic modifier and 100mL of DMF, and reacted at 80℃ for 6 hours under N2 protection to obtain modified chopped basalt fiber.

[0056] Example 4: The high-temperature resistant organic modifier was prepared by the following steps:

[0057] Add 15.1g of aminopropyl double-ended compound and 100mL of tetrahydrofuran to a three-necked flask, purge with nitrogen for protection, add 17.1g of p-hydroxybenzaldehyde and 0.1g of anhydrous sodium sulfate, and react at 60℃ for 8h to obtain intermediate 1. Add 4.5g of p-aminochlorobenzene and 80mL of tetrahydrofuran to a three-necked flask, add 9.5g of 40% formaldehyde solution under ice-water bath conditions, stir for 0.5h, add 6.3g of intermediate 1, and react at 60℃ for 10h to obtain intermediate 2. Add 20.4g of 4-nitrobenzaldehyde, 27.8g of nitrobenzene, 13.2g of ammonium acetate, and 70mL of acetic anhydride to a three-necked flask, heat to 125℃ for 3h to obtain intermediate 3. Add 8.7g of intermediate 3 and 6.3g of... 4-Nitro-o-phenylenediamine, 0.9 g copper bromide, and 110 mL n-butanol were heated to 110 °C and reacted for 13 h. The mixture was then reduced with hydrogen gas to obtain intermediate 4. Intermediate 4, intermediate 2, potassium carbonate, and toluene were added to a three-necked flask, and the mixture was heated to 60 °C and reacted for 5 h to obtain a high-temperature resistant organic modifier. The molar ratio of intermediate 4 to intermediate 2 was 1:1, and the amount of potassium carbonate was 10% of the mass of intermediate 4.

[0058] Example 5: The high-temperature resistant organic modifier was prepared by the following steps:

[0059] Add 15.8 g of aminopropyl double-ended compound and 110 mL of tetrahydrofuran to a three-necked flask, purge with nitrogen, add 17.4 g of p-hydroxybenzaldehyde and 0.12 g of anhydrous sodium sulfate, and react at 62 °C for 9 h to obtain intermediate 1. Add 4.8 g of p-aminochlorobenzene and 90 mL of tetrahydrofuran to a three-necked flask, add 9.8 g of 43% formaldehyde solution under ice-water bath conditions, stir for 0.7 h, add 6.7 g of intermediate 1, and react at 63 °C for 12 h to obtain intermediate 2. Add 20.8 g of 4-nitrobenzaldehyde, 28.2 g of nitrobenzene, 13.3 g of ammonium acetate and 80 mL of acetic anhydride to a three-necked flask, heat to 127 °C and react for 3 h to obtain intermediate 3. Add 9.1 g of intermediate 3 and 6.5 g of... 4-Nitro-o-phenylenediamine, 1g of copper bromide, and 115mL of n-butanol were heated to 113℃ and reacted for 13h. The mixture was then reduced by hydrogen gas to obtain intermediate 4. Intermediate 4, intermediate 2, potassium carbonate, and toluene were added to a three-necked flask, and the mixture was heated to 65℃ and reacted for 6h to obtain a high-temperature resistant organic modifier. The molar ratio of intermediate 4 to intermediate 2 was 1:1, and the amount of potassium carbonate was 12% of the mass of intermediate 4.

[0060] Example 6: The high-temperature resistant organic modifier was prepared by the following steps:

[0061] Add 16.5g of aminopropyl double-ended compound and 120mL of tetrahydrofuran to a three-necked flask, purge with nitrogen, add 17.8g of p-hydroxybenzaldehyde and 0.13g of anhydrous sodium sulfate, and react at 65℃ for 10h to obtain intermediate 1. Add 5.2g of p-aminochlorobenzene and 100mL of tetrahydrofuran to a three-necked flask, add 10g of 45% formaldehyde solution under ice-water bath conditions, stir for 1h, add 7.2g of intermediate 1, and react at 65℃ for 12h to obtain intermediate 2. Add 21.3g of 4-nitrobenzaldehyde, 28.5g of nitrobenzene, 13.5g of ammonium acetate, and 90mL of acetic anhydride to a three-necked flask, heat to 130℃ and react for 4h to obtain intermediate 3. Add 9.4g of intermediate 3 and 6.7g of... 4-Nitro-o-phenylenediamine, 1g of copper bromide, and 120mL of n-butanol were heated to 115℃ and reacted for 14h. The mixture was then reduced by hydrogen gas to obtain intermediate 4. Intermediate 4, intermediate 2, potassium carbonate, and toluene were added to a three-necked flask, and the mixture was heated to 70℃ and reacted for 8h to obtain a high-temperature resistant organic modifier. The molar ratio of intermediate 4 to intermediate 2 was 1:1, and the amount of potassium carbonate was 15% of the mass of intermediate 4.

[0062] Example 7: A reinforced high-temperature wear-resistant and refractory castable, comprising the following raw materials in parts by weight:

[0063] 84.5 parts high-alumina bauxite, 21.4 parts andalusite, 32.5 parts silica powder, 23.8 parts silicon nitride powder, 6.8 parts aluminum tripolyphosphate, 6.3 parts alumina powder, 1.5 parts attapulgite clay, 11.5 parts calcium aluminate cement, 15.6 parts modified short-cut basalt fiber, 5.7 parts sodium tripolyphosphate, and 1.5 parts silica sol;

[0064] This reinforced high-temperature wear-resistant and refractory castable is made by the following steps:

[0065] Step A1: Add high-alumina bauxite and andalusite into a mixer and mix for 10 minutes to obtain mixed aggregate, wherein the particle size of high-alumina bauxite is 1 mm, the alumina content is ≥80%wt, and the particle size of andalusite is ≤1 mm.

[0066] In step A2, silica micro powder, silicon nitride micro powder, aluminum tripolyphosphate, alumina micro powder, attapulgite clay, calcium aluminate cement, silica sol, sodium tripolyphosphate, and modified short-cut basalt fiber are ball-milled evenly to obtain a mixed powder, wherein the particle size of silica micro powder is ≤0.065mm, the particle size of silicon nitride micro powder is ≤0.06mm, and the particle size of alumina micro powder is ≤3μm.

[0067] Step A3: Add the mixed powder to the mixed aggregate, mix evenly, then add 2% water by weight of the total raw materials and stir to form a mud. Place the mud into a mold, vibrate and cast it into shape. After hardening at room temperature, demold it, dry at 120℃ for 12 hours, and cool naturally to room temperature to obtain the green body.

[0068] Step A4: Sinter the green body at 1300℃ for 20 hours to obtain the reinforced high-temperature wear-resistant refractory castable.

[0069] Example 8: A reinforced high-temperature wear-resistant and refractory castable, comprising the following raw materials in parts by weight:

[0070] 88.1 parts high-alumina bauxite, 23.2 parts andalusite, 35.4 parts silica powder, 25.2 parts silicon nitride powder, 7.3 parts aluminum tripolyphosphate, 8.15 parts alumina powder, 2.5 parts attapulgite clay, 18.9 parts calcium aluminate cement, 16.7 parts modified short-cut basalt fiber, 6.2 parts sodium hexametaphosphate, and 2.4 parts silica sol;

[0071] This reinforced high-temperature wear-resistant and refractory castable is made by the following steps:

[0072] Step A1: Add high-alumina bauxite and andalusite into a mixer and mix for 12 minutes to obtain mixed aggregate, wherein the particle size of high-alumina bauxite is 1 mm, the alumina content is ≥80%wt, and the particle size of andalusite is ≤1 mm.

[0073] In step A2, silica micro powder, silicon nitride micro powder, aluminum tripolyphosphate, alumina micro powder, attapulgite clay, calcium aluminate cement, silica sol, sodium tripolyphosphate, and modified short-cut basalt fiber are ball-milled evenly to obtain a mixed powder, wherein the particle size of silica micro powder is ≤0.065mm, the particle size of silicon nitride micro powder is ≤0.06mm, and the particle size of alumina micro powder is ≤3μm.

[0074] Step A3: Add the mixed powder to the mixed aggregate, mix evenly, then add 6% water by weight of the total raw materials and stir to form a mud, put it into a mold, vibrate and cast to form a shape, demold after hardening at room temperature, dry at 130℃ for 18 hours, and cool naturally to room temperature to obtain a green body;

[0075] Step A4: Sinter the green body at 1400℃ for 25 hours to obtain the reinforced high-temperature wear-resistant refractory castable.

[0076] Example 9: A reinforced high-temperature wear-resistant and refractory castable, comprising the following raw materials in parts by weight:

[0077] 93.6 parts high-alumina bauxite, 25.3 parts andalusite, 37.8 parts silica powder, 26.2 parts silicon nitride powder, 9.2 parts aluminum tripolyphosphate, 10.5 parts alumina powder, 3.2 parts attapulgite clay, 22.4 parts calcium aluminate cement, 18.4 parts modified short-cut basalt fiber, 6.5 parts sodium polyacrylate, and 3.2 parts silica sol;

[0078] This reinforced high-temperature wear-resistant and refractory castable is made by the following steps:

[0079] Step A1: Add high-alumina bauxite and andalusite into a mixer and mix for 15 minutes to obtain mixed aggregate, wherein the particle size of high-alumina bauxite is 2mm, the alumina content is ≥80%wt, and the particle size of andalusite is ≤1mm.

[0080] In step A2, silica micro powder, silicon nitride micro powder, aluminum tripolyphosphate, alumina micro powder, attapulgite clay, calcium aluminate cement, silica sol, sodium tripolyphosphate, and modified short-cut basalt fiber are ball-milled evenly to obtain a mixed powder, wherein the particle size of silica micro powder is ≤0.065mm, the particle size of silicon nitride micro powder is ≤0.06mm, and the particle size of alumina micro powder is ≤3μm.

[0081] Step A3: Add the mixed powder to the mixed aggregate, mix evenly, then add water (8% of the total weight of the raw materials) and stir to form a mud. Place the mud into a mold, vibrate and cast it into shape. After hardening at room temperature, demold it, dry at 140℃ for 20 hours, and cool naturally to room temperature to obtain the green body.

[0082] Step A4: Sinter the green body at 1500℃ for 28 hours to obtain the reinforced high-temperature wear-resistant refractory castable.

[0083] Comparative Example 1: Refractory castable produced by Langfang Lvxiang Environmental Protection Technology Co., Ltd.

[0084] Comparative Example 2: The preparation method of the castable in Comparative Example 2 is the same as that in Example 7, except that no modified short-cut basalt fibers are added.

[0085] The refractory castables obtained in Examples 7-9 and Comparative Examples 1-2 were tested for flexural strength according to GB / T3002-2004 "Test Method for High Temperature Flexural Strength of Refractory Materials" (testing the flexural strength of the material at high temperature in a high-temperature furnace (e.g., 1400℃, 1500℃) to simulate the actual use environment); and their compressive strength was tested according to YB / T2202-1998 "Test Method for High Temperature Compressive Strength of Refractory Castables" (testing the compressive strength of the material at high temperature (1100℃, 1300℃)). The results are shown in Table 1.

[0086] Table 1

[0087]

[0088]

[0089] As shown in Table 1, compared with Comparative Examples 1-2, the refractory castables prepared in Examples 7-9 have higher strength and heat resistance.

[0090] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0091] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

Claims

1. A reinforced high temperature abrasion resistant castable refractory characterized in that, The raw materials include the following weight parts: high bauxite 84.5-93.6 parts, andalusite 21.4-25.3 parts, silicon oxide micro powder 32.5-37.8 parts, silicon nitride micro powder 23.8-26.2 parts, aluminum tripolyphosphate 6.8-9.2 parts, aluminum oxide micro powder 6.3-10.5 parts, attapulgite clay 1.5-3.2 parts, calcium aluminate cement 11.5-22.4 parts, modified short basalt fiber 15.6-18.4 parts, water reducing agent 5.7-6.5 parts, and silica sol 1.5-3.2 parts; The modified short basalt fiber is prepared by the following steps: The short basalt fiber is reacted with the high-temperature resistant organic modifier at 60-80 DEG C for 4-6 hours to obtain the modified short basalt fiber; The high-temperature resistant organic modifier is prepared by the following steps: Step S1, ammonia propyl double end cap, tetrahydrofuran are added into a three-necked flask, nitrogen is passed for protection, p-hydroxybenzaldehyde, anhydrous sodium sulfate are added, and the temperature is raised to 60-65 DEG C for reaction for 8-10 h to obtain intermediate 1; Step S2, p-amino chlorobenzene, tetrahydrofuran are added into a three-necked flask, 40%-45% mass fraction of formaldehyde solution is added under ice water bath condition, stirring is carried out for 0.5-1 h, intermediate 1 is added, the temperature is raised to 60-65 DEG C, and reaction is carried out for 10-12 h to obtain intermediate 2; Step S3, 4-nitrobenzaldehyde, nitroethane, ammonium acetate, acetic anhydride are added into a three-necked flask, heating is carried out to 125-130 DEG C for reaction for 3-4 h to obtain intermediate 3; Step S4, intermediate 3, 4-nitro-o-phenylenediamine, copper bromide, n-butanol are added into a three-necked flask, heating is carried out to 110-115 DEG C for reaction for 13-14 h, hydrogen reduction is carried out to obtain intermediate 4; Step S5, intermediate 4, intermediate 2, potassium carbonate, toluene are added into a three-necked flask, the temperature is raised to 60-70 DEG C, and reaction is carried out for 5-8 h to obtain the high-temperature resistant organic modifier.

2. A reinforced high temperature refractory castable according to claim 1, characterized in that: The particle size of the high bauxite is 1-2 mm, and the content of aluminum oxide is ≥80%wt; the particle size of the andalusite is ≤1 mm; the particle size of the silicon oxide micro powder is ≤0.065 mm; the particle size of the silicon nitride micro powder is ≤0.06 mm; and the particle size of the aluminum oxide micro powder is ≤3 μm.

3. A reinforced high temperature refractory castable according to claim 1, characterized in that: The water reducing agent is one of sodium tripolyphosphate, sodium hexametaphosphate, sodium polyacrylate, and sodium lignosulfonate.

4. A process for the preparation of a reinforced high temperature refractory and castable according to claim 1, characterized in that: The preparation steps include the following steps: Step A1, the high bauxite and the andalusite are mixed and stirred for 10-15 min to obtain mixed aggregates; Step A2, the silicon oxide micro powder, the silicon nitride micro powder, the aluminum tripolyphosphate, the aluminum oxide micro powder, the attapulgite clay, the calcium aluminate cement, the silica sol, the water reducing agent, and the modified short basalt fiber are uniformly ball milled to obtain mixed powder; Step A3, the mixed powder and the mixed aggregates are uniformly mixed, 2-8% of water based on the total weight of the raw materials is added, and stirring is carried out to obtain a mud material, which is placed into a mold, cast into a shape, demolded after casting, dried at 120-140 DEG C for 12-20 h, and naturally cooled to room temperature to obtain a green body; Step A4, the green body is sintered at 1300-1500 DEG C for 20-28 h to obtain the reinforced high-temperature resistant and wear-resistant castable refractory.

Citation Information

Patent Citations

  • High-alumina refractory castable and preparation method thereof

    CN108046784A

  • Heat-insulating refractory castable and preparation method thereof

    CN118324499A